2013
DOI: 10.4103/1817-1737.114285
|View full text |Cite
|
Sign up to set email alerts
|

Gastrobronchial fistula a rare complication post laparoscopic sleeve gastrectomy

Abstract: Gastrobronchial fistula is a rare but serious complication of laparoscopic sleeve gastrectomy with significant morbidity and mortality. We present the case of a 30-year-old man who underwent laparoscopic sleeve gastrectomy for morbid obesity and presented later with a history of chronic productive cough. Upper gastrointestinal series showed the presence of a communicating fistula between the stomach and the left lung bronchial tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…[4][5][6] Timing of the first presentation also of the BGF post-surgery is one of the factors that is reported differently in the surgical literature, that could be as early as 1-month post-op but a late presentation (>3 months) is more common, with mean timing of (6.7 months). 3,[5][6][7][8][9] What is unique about our case report is that we report a patient who is a known case of SLE with CNS involvement taking immune suppressive and steroid medications. Despite the evidence that suggest patients with SLE are more prone to have surgical complications post-operatively, the newly emerging data in the surgical literature suggest a major benefit of obesity surgery with the expected weight loss for patients with SLE, as Corcelles et al have concluded in their retrospective analysis of patients with SLE who underwent obesity surgery in Cleveland clinic, they analyzed 31 patient who had received different types of anti-obesity intervention, out of that (42%) of patients reported to have reduction in the number of medications used to treat SLE, (32%) experienced reduction in the dose of steroids and (19%) stopped taking any steroid medication, so with that in mind our patient was indicated to have the benefit from the weight loss postoperatively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[4][5][6] Timing of the first presentation also of the BGF post-surgery is one of the factors that is reported differently in the surgical literature, that could be as early as 1-month post-op but a late presentation (>3 months) is more common, with mean timing of (6.7 months). 3,[5][6][7][8][9] What is unique about our case report is that we report a patient who is a known case of SLE with CNS involvement taking immune suppressive and steroid medications. Despite the evidence that suggest patients with SLE are more prone to have surgical complications post-operatively, the newly emerging data in the surgical literature suggest a major benefit of obesity surgery with the expected weight loss for patients with SLE, as Corcelles et al have concluded in their retrospective analysis of patients with SLE who underwent obesity surgery in Cleveland clinic, they analyzed 31 patient who had received different types of anti-obesity intervention, out of that (42%) of patients reported to have reduction in the number of medications used to treat SLE, (32%) experienced reduction in the dose of steroids and (19%) stopped taking any steroid medication, so with that in mind our patient was indicated to have the benefit from the weight loss postoperatively.…”
Section: Discussionmentioning
confidence: 93%
“…5 The number of papers reporting successful conservative management is increasing in the surgical literature, Abraham and colleges reported endoscopic management of BGF with self-expanding plastic stent and ablation of the fistula tract with no method mentioned and for how long patient was followed up, Al Harbi et al, in the other hand reported endoscopic management with a covered stent, also did Al Lehibi et al, with reporting of 1 year follow up showing no recurrence. [7][8][9] In the 15 patients that were enrolled in the retrospective study done by Campos et al, the endoscopic management of BGF had 2 main principles: correction of the distal gastric stricture and the internal opening of gastric fistula, and of the patients enrolled in the study (5) had laparoscopic sleeve gastrectomy, out that of them (4) patients had in addition to the BGF a narrowing at the level of incisura angularis and one patient had the narrowing at the level of the ring, they reported endoscopic dilation of the narrowing by 30 mm pneumatic dilator, endoscopic internal drainage of pulmonary collection and placement of self-expanding plastic stent if required, in their results (14 of 15) had benefited from the endoscopic management without going for more aggressive management and of that 7 patients had management with stenting which resulted in faster mean time recovery from the BGF (2.5 months in compare to 9.5 months We recommend that patients who is known case of systemic disease (like SLE in our case) who undergoes anti-obesity surgery should be followed life long, and inpatient who develop BGF post laparoscopic sleeve gastrectomy conservative management could be a reasonable option that could offered to the patient despite the prolonged period of time in the light of the current evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This is the only case study that describes fistula formation occurring after a robotic-assisted laparoscopic repair of a chronic diaphragmatic hernia, as most gastrobronchial fistulas from an operation have been described after laparoscopic sleeve gastrectomies [9].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic inflammation and infection will then spread by lymphatic flow from below to above the diaphragm or by directly eroding through the diaphragm, causing a lung abscess that eventually drains into a bronchus [13]. Some authors advocate for less severe cases, a more conservative approach by management with wide-spectrum antibiotics, CT-guided percutaneous drainage of any subphrenic collection, endoscopic covered stent of gastric fistula, and nasojejunostomy feeding [10,11,14]. However, our expert opinion, based on carefully evaluating the severity of our case (massive weight loss, low nutritional status, and multiple sepsis episodes), was for a more definitive treatment approach.…”
Section: Discussionmentioning
confidence: 99%